Advancing the evidence base for public policies impacting on dietary behaviour, physical activity and sedentary behaviour in Europe: The Policy Evaluation Network promoting a multidisciplinary approach. (October 2020) - Lakerveld, Jeroen; Woods, Catherine; Hebestreit, Antje; Brenner, Hermann; Flechtner-Mors, Marion; Harrington, Janas M.; Kamphuis, Carlijn B.M.; Laxy, Michael; Luszczynska, Aleksandra; Mazzocchi, Mario; Murrin, Celine; Poelman, Maartje; et al.
Highlights: 28 research institutes have joined in the Policy Evaluation Network (PEN). PEN studies EU policies on diet, physical activity and sedentary behaviours. PEN advances knowledge on impact and effective implementation of these policies. We here describe the rationale and specific goals of PEN, and highlight innovations. Abstract: Non-communicable diseases (NCDs) are the leading cause of global mortality. As the social and economic costs of NCDs have escalated, action is needed to tackle important causes of many NCD's: low physical activity levels and unhealthy dietary behaviours. As these behaviours are driven by upstream factors, successful policy interventions are required that encourage healthy dietary behaviours, improve physical activity levels and reduce sedentary behaviours of entire populations. However, to date, no systematic research on the implementation and evaluation of policy interventions related to these health behaviours has been conducted across Europe. Consequently, no information on the merit, gaps, worth or utility of cross-European policy interventions is available, and no guidance or recommendations on how to enhance this knowledge across European countries exists. As part of the Joint Programming Initiative "A Healthy Diet for a Healthy Life" (JPI HDHL), 28 research institutes from seven European countries and New Zealand have combined their expertise to form the Policy Evaluation Network (PEN). PEN's aim is to advance tools to identify, evaluate, implement and benchmark policies designed to directly or indirectly target dietary behaviours, physical activity, and sedentary behaviour in Europe, as well as to understand how these policies increase or decrease health inequalities. Using well-defined evaluation principles and methods, PEN will examine the content, implementation and impact of policies addressing dietary behaviour, physical activity levels and sedentary behaviour across Europe. It will realise the first steps in a bespoke health policy monitoring and surveillance system for Europe, and refine our knowledge of appropriate research designs and methods for the quantification of policy impact. It will contribute to our understanding of how to achieve successful transnational policy implementation and monitoring of these policies in different cultural, demographic or socioeconomic settings. PEN will consider equity and diversity aspects to ensure that policy actions are inclusive and culturally sensitive. Finally, based on three policy cases, PEN will illustrate how best to evaluate the implementation and impact of such policies in order to yield healthy diets and activity patterns that result in healthier lives for all European citizens.